Effect Of The Addition Of Andaliman Powder (Zanthoxylum acanthopodium) On The Chemical And Organoleptic Characteristics Of Moringa Tempe Nuggets - Yosi Rosalinda Siregar; Yoakhim Y.E. Oessoe; Tineke Marlyn Langi (Jurnal Agroekoteknologi Terapan, 2023)
The purpose of this study is to analyze the sensory and chemical characteristics of Moringa tempeh nuggets with the addition of andaliman powder. Nuggets are ready-to-eat food products that are easy to find and always available, this study used the Complete Randomized Design (RAL) research method with the treatment of adding andaliman powder for each treatment of 3 repeats, namely, A1 treatment (2g), A2 treatment (4g), A3 treatment (6g), A4 treatment (8g), A5 treatment (10g). The parameters tested were sensory characteristics (color, taste, aroma, and texture), and Chemical characteristics (moisture content, proteins, and fats). Based on the results of chemical and sensory analysis, the panelists' level of favorability for Moringa tempeh nuggets with the addition of andaliman powder, namely color 3.8–4.63 (neutral-somewhat like), taste 4.4-5.03 (neutral-somewhat like), aroma 4.6-5.23 (somewhat like), texture 3.93–4.9 (neutral-somewhat like), with water content (30.33%), protein content (21.89%), fat (3.75%). Keywords: Moringa Tempe Nuggets, Andaliman Powder Abstrak Tujuan dari penelitian ini adalah untuk menganalisis karakteristik sensoris dan kimia nugget tempe kelor dengan penambahan bubuk andaliman. Nugget merupakan produk makanan siap saji yang mudah ditemui dan selalu tersedia. Penelitian ini menggunakan metode penelitian Rancangan Acak Lengkap (RAL) dengan perlakuan penambahan bubuk andaliman masing-masing perlakuan 3 kali pengulangan yaitu, perlakuan A1 (2g), perlakuan A2 (4g), perlakuan A3 (6g), perlakuan A4 (8g), perlakuan A5 (10g). Parameter yang diuji adalah karakteristik sensoris (warna, rasa, aroma, dan tekstur), dan Karakteristik kimia (kadar air, protein, dan lemak). Berdasarkan hasil analisis kimia dan sensoris tingkat kesukaan panelis terhadap nugget tempe kelor dengan penambahan bubuk andaliman, yaitu warna 3,8–4,63 (netral-agak suka), rasa 4,4-5,03 (netral-agak suka), aroma 4,6-5,23 (agak suka), tekstur 3,93– 4,9 (netral-agak suka), dengan kadar air (30,33%), kadar protein (21,89 %), lemak (3,75%). Kata kunci: Nugget Tempe Kelor, Bubuk Andaliman.